The contributions of smartphone applications in supporting junior high school students’ learning activities - Anggun Fitriana Dewi; Sumardi Sumardi; Ngadiso Ngadiso (Universitas Ahmad Dahlan)
In the last few decades, the development of mobile phone is rapidly growing and brings many changes in human life. Mobile phones nowadays extend their capabilities into all aspects in human life, including teaching and learning process. Therefore, this research aims at knowing what smartphone applications are frequently used by the students and investigating the contributions of those applications in students’ learning activities. This research uses a qualitative case study in order to obtain a deep analysis. The subjects of this research are twenty students of junior high school in Kebumen who are chosen based on some criteria. Additionally, the data of this research were obtained using questionnaire and interview. Based on the finding, the smartphone applications which are most frequently used by the students to support their learning activities are social media (Instagram, Facebook, and Twitter), Google chrome, music player, offline dictionary, YouTube, and English exercise application from play store. Last but not least, all the students agree that smartphone applications give positive contributions to their learning process. The contributions of those applications in the students’ learning activities are helping the students in finding more sources of authentic English materials; finding more exercise in grammar, reading, listening, speaking, and writing skills; improving students’ vocabulary, grammar, listening, and speaking skill.